Force-velocity relationship of single actin filament interacting with immobilised myosin measured by electromagnetic technique. - Holohan,S-JP; Marston,SB (IEE Proc Nanobiotechnol, 2005)
The effect of applying an external load to actin filaments moving in the in vitro motility assay is studied. Bead-tailed actin filaments were made by polymerising actin onto 2.8 microm diameter Dynabeads conjugated with gelsolin-G actin. These were introduced into a motility cell coated with 100 microg/ml rabbit fast skeletal myosin in the presence of ATP and 0.5% methylcellulose. The motility cell was inserted between the pole-pieces of an electromagnet and the fluorescent beads and filaments were observed. The force-current relationship of the electromagnet was determined from the velocity of free beads in viscous solution and Stokes' equation. The magnet produced up to 6 pN force on the Dynabeads at 1 A. Many bead-tailed actin filaments stuck to the surface, but the beads that did move moved at the same speed as unloaded f-actin in the same cell. Bead-tailed filaments slowed down under an increasing magnetic load, eventually stalled and then slid backward under increasing load before detaching from the surface. Single-filament force-velocity curves were constructed and a stalling force of about 0.6 pN/mm of actin filament estimated.